Women's Political Representation in Iran and Turkey Demanding a Seat at the Table - Tajali, Mona (Edinburgh University Press, 2023)
How have women in many Muslim-majority countries been able to achieve surprising success despite the significant constraints imposed by conservative gender ideology and authoritarian political parties and systems? Through a comparative focus on Iran and Turkey, Mona Tajali examines the activities and strategies of women's rights groups across the ideological spectrum. She explores how various groups have negotiated with political elites in order to bolster female political representation and identifies the conditions that stimulate greater support to ease women's path to political office. Studying how women's groups manoeuvre within these structures is important to help our understanding of the gendered politics of autocratic regimes.